Case report: The presence of third-degree atrioventricular block caused by pulmonary embolism masquerading as acute ST-segment elevation myocardial infarction - Ma, Min; Liang, Shichu; He, Yong; Wang, Hua (Frontiers in Cardiovascular Medicine, 2023)
Background Pulmonary embolism (PE) typically presents with chest pain, tachypnea, hemoptysis, syncope, and increased markers of myocardial injury. On an electrocardiogram (ECG), sinus tachycardia, right bundle branch block (RBBB), S1Q3T3 pattern, and/or precordial T-wave inversion may be observed. Despite being one of the common causes of chest pain, a third-degree atrioventricular block (III° AVB) is rare in cases of PE, which can lead to difficulties in diagnosis or even overlooking this condition. Case summary In this case report, we present a patient who was transferred to our hospital with suspected acute myocardial infarction (AMI). The patient's ECG showed ST-segment elevation in the inferior wall and a III° AVB, combined with significantly increased markers of myocardial injury. Interestingly, the patient also had a history of cerebral hemorrhage (ICH) for 7 days prior to being transferred to our hospital. After undergoing a systematic examination and evaluation, the final diagnosis for the patient was PE. Conclusions In addition to considering common symptoms, it is important not to overlook rare symptoms when diagnosing a disease. This case serves as an example of how the misdiagnosis rate for PE can be reduced by conducting a comprehensive clinical evaluation and paying attention to all clinical clues and examination results.